Numerical modeling of solar wind and coronal mass ejection in the inner heliosphere: A review - Zhang, Man; Feng, Xueshang; Li, Huichao; Xiong, Ming; Shen, Fang; Yang, Liping; Zhao, Xinhua; Zhou, Yufen; Liu, Xiaojing (Frontiers in Astronomy and Space Sciences, 2023)
The predictions of plasma parameters in the interplanetary medium are the core of space weather forecasts, and the magnetohydrodynamics (MHD) numerical simulation is an important tool in the prediction of plasma parameters. Operational space weather forecasts are commonly produced by a heliosphere model whose inner boundary is set at 18 R$_s$ or beyond. Such predictions typically use empirical/physics-based inner boundary conditions to solve the MHD equations for numerical simulation. Numerical modeling of the inner heliosphere has experienced significant progress in the recent years. In this paper, the numerical modeling of solar wind and coronal mass ejection in the inner heliosphere is reviewed, in particular, the different inner boundary conditions used in the simulation are investigated since the MHD solutions are predetermined by the treatment of the inner boundary conditions to a large extent. Discussion is made on further development of the heliosphere model.